Current trends in etiology, prognosis and therapeutic aspects of Parkinson’s disease: a review - Jagadeesan, A. J.; Murugesan, R; Vimala Devi, S; Meera, M.; Madhumala, G.; Vishwanathan Padmaja, M.; Ramesh, A.; Banerjee, A.; Sushmitha, S.; Khokhlov, A. N.; Marotta, F.; Pathak, Surajit (Acta Biomedica Atenei Parmensis, 2017)
Parkinson’s disease (PD) is a movement disorder, mainly affecting population consisting of the aged. PD occurs chiefly due to progressive loss of dopaminergic neurons in nigrostriatal pathway. Largely, PD patients suffer from non-motor symptoms, such as depression, anxiety, fatigue, and sleep disorders, that needs further investigation and addressing during PD research. Depression in PD is a predominant and complex symptom, and its pathology exists extrinsic to the nigrostriatal system. This disease can ultimately be managed by a combination of regular physiotherapy and proper medication. Taking together the present scenario of PD, including the nature of disease, characteristics, treatment, diagnosis of the patients with PD, these outcomes were reviewed to be explored along with many speech-based solutions to PD in this study. This neurodegenerative disorder needs advancement in research and development which can help patients with PD to lead a normal life.